Mannose-binding lectin insufficiency is associated with airway Haemophilus colonization and a higher risk of post-RSV bronchiolitis recurrent wheezing - Zhang, Xiaoyan; Zhang, Xiang; Wang, Xinglan; Tang, Xiaolei; Xu, Hui; Zhang, Nan; Zhao, Shunying; Yang, Haiming; He, Qiushui (John Wiley & Sons, 2026)
Objective
To investigate whether mannose-binding lectin (MBL) insufficiency influences the airway microbiota composition and development of subsequent recurrent wheezing in infants with severe respiratory syncytial virus (RSV) bronchiolitis.
Methods
Sixty-seven infants who were hospitalized during an initial episode of severe RSV bronchiolitis at 6 months of age or less were included in the study and followed up until the age of 3 years. Serum and sputum samples were collected. The serum MBL concentrations were determined by ELISA; the sputum microbiota and cytokines were analyzed by 16S rRNA-based sequencing and multiplex immunoassay, respectively.
Results
Twenty-six infants developed recurrent wheezing by the age of 3 years, and 41 did not. The rate of MBL insufficiency was significantly higher among infants who developed recurrent wheezing compared to those who did not [50.0% (13/26) vs. 24.4% (10/41), (p = .031)]. MBL insufficiency was independently associated with a higher risk of subsequent development of recurrent wheezing (adjusted Odds Ratio: 3.5, 95% CI 1.1–12.3, p = .035). Haemophilus was found to be the most discriminative genus between infants with and without MBL insufficiency (LDA >4.0). The level of INF-γ (p = .019) in infants with MBL insufficiency was significantly lower than that among infants with normal MBL.
Conclusion
During the first episode of severe RSV bronchiolitis in infants <6 months of age, MBL insufficiency was associated with a higher risk of developing subsequent recurrent wheezing by age three. Infants with MBL insufficiency were more likely to be colonized with Haemophilus and have weaker airway IFN-γ response.